The Impact of MSME’s on Employment, Investment, and Income - Albert Gamot Malau; Mahjus Ekananda (Universitas Negeri Semarang, 2025)
North Sumatra, a key economic region in Indonesia outside of Java, continues to face persistent challenges such as high unemployment, the dominance of the informal sector, and uneven economic growth. Within this context, Micro, Small, and Medium Enterprises (MSMEs) serve as a cornerstone of the regional economy, particularly through their role in labor absorption and income generation. Despite their significance, MSMEs in North Sumatra still face substantial obstacles, including limited access to financing, inconsistent investment growth, and inadequate policy implementation—factors that hinder their full potential in driving inclusive development. This study examines the dynamic relationship between MSME growth, workforce participation, and Gross Regional Domestic Product (GRDP) in North Sumatra, employing a simultaneous equation model with time-series data from 2009 to 2023. The Two-Stage Least Squares (2SLS) method addresses endogeneity and simulates the effects of policy interventions projected for the 2025–2030 period. The findings indicate that MSME development is significantly influenced by policy instruments such as tax incentives and minimum wage regulations. Increases in wages and tax reductions enhance labor absorption, stimulate MSME performance, and promote GRDP growth. The study provides practical policy insights for strengthening the resilience and sustainability of MSMEs within North Sumatra’s evolving economy.